Instituciones eclesiásticas y crédito en Antioquia, siglo XVIII (2016)
ABSTRACT: In a mining and agrarian society, and in the absence of commercial banking, pious institutions, covered by Catholic Church, became an important source of loans and money. This paper will present the type of pious institutions involved, and the economic areas of the province of Antioquia that were benefited with the investment of those resources. This information can be found in affidavits from the colonial period. Keywords: pious works, credit, ground loans, investments.